2014
DOI: 10.2472/jsms.63.250
|View full text |Cite
|
Sign up to set email alerts
|

Seismic-Derived Quality Factor for Lithology Classification around the Median Tectonic Line

Abstract: We calculated quality factor from seismic reflection data in order to classify the lithology around the Median Tectonic Line (MTL). Since seismic velocity around the MTL was not accurately estimated, it was difficult to classify the lithology and characterize the MTL. To calculate quality factor from seismic data, we used two methods: (1) spectral ratio method and (2) peak frequency method. In this study, we applied these two methods for the multi-channel seismic reflection data as well as zero-offset Vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It is suggested that the Kawakami fault was originally formed as a non-vertical reverse fault, and subsequent dextral strike-slip displacement occurred along the same fault plane. In this study area, previous seismic reflection surveys indicated a clear reflector dipping 30° to the north (Shigei et al 2014). This is consistent with the north-dipping MTLTB, which juxtaposed the Izumi Group against the Sanbagawa metamorphic rocks.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is suggested that the Kawakami fault was originally formed as a non-vertical reverse fault, and subsequent dextral strike-slip displacement occurred along the same fault plane. In this study area, previous seismic reflection surveys indicated a clear reflector dipping 30° to the north (Shigei et al 2014). This is consistent with the north-dipping MTLTB, which juxtaposed the Izumi Group against the Sanbagawa metamorphic rocks.…”
Section: Discussionsupporting
confidence: 87%
“…Active dextral MTL fault structures are typically observed on Shikoku (Okada 1970;Tsutsumi and Okada 1996;Goto and Nakata 2000). Detailed geological mapping (e.g., Takahashi 1992;Kubota and Takeshita 2007;Shigematsu et al 2012;Aoya et al 2013) and seismic reflection surveys (e.g., Ito et al 1996;Tsutsumi et al 2007;Shigei et al 2014) have distinguished the high-angle MTL active fault zone (MTLAFZ) from the low-angle inherited MTL geological terrane boundary fault (MTLTB). The MTLTB and the MTLAFZ run subparallel to each other in central Shikoku (Fig.…”
Section: Geological Settingsmentioning
confidence: 99%
“…The other is the lithological boundary fault between Ryoke metamorphic rocks and Sambagawa metamorphic rocks (the material boundary MTL: MBMTL). Multichannel seismic data were acquired along a 1-km survey line with ~4-m receiver spacing and ~2-m source spacing as part of a reflection survey in an investigation of fault geometry Table 1 Parameters of P-SV finite-difference modeling for the simulated models Note that the time interval is 0.08 ms and the number of time steps is 25,000 in the simulation for the inverted velocity model by Ikeda et al (2013) Size of on the MTL (Shigei et al 2014). An impactor was used as a seismic source, and 30 Hz geophones were used as a receiver.…”
Section: Application To Field Datamentioning
confidence: 99%